2015
DOI: 10.1136/bcr-2014-206734
|View full text |Cite
|
Sign up to set email alerts
|

Complete resolution of the symptoms of refractory Osgood-Schlatter disease following percutaneous fixation of the tibial tuberosity

Abstract: SUMMARYOsgood-Schlatter disease is a common cause of anterior knee pain in adolescents. In a good proportion of cases the pain is relieved through stopping sport alone, or by doing so in conjunction with undertaking physiotherapy. However, resolution of symptoms may take several years. A proportion of teenagers are prevented from participating in sport for a prolonged period as a result of the condition, and some have persisting knee pain into adulthood. We report the use of a new surgical treatment for this d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Despite that favorable natural progress has been recognized as a self-limiting disease in 90% of the patients, severe pain in the tibial tuberosity and difficulties in daily life are often complained by athletes or military personnel who frequently perform activities that cause stress on the knee joint regardless of the completion of the growth 2) . Various treatment methods including surgical treatment have been performed for the patients with severe symptoms refractory to conservative treatment 2 3 4 5 6 7 8) ; however, cases where the symptoms persist even after surgical treatment have often been reported 3 4 9 10 11 12) . This has been thought to be due to the lack of research on pathophysiology and clinical progress of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Despite that favorable natural progress has been recognized as a self-limiting disease in 90% of the patients, severe pain in the tibial tuberosity and difficulties in daily life are often complained by athletes or military personnel who frequently perform activities that cause stress on the knee joint regardless of the completion of the growth 2) . Various treatment methods including surgical treatment have been performed for the patients with severe symptoms refractory to conservative treatment 2 3 4 5 6 7 8) ; however, cases where the symptoms persist even after surgical treatment have often been reported 3 4 9 10 11 12) . This has been thought to be due to the lack of research on pathophysiology and clinical progress of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…O sgood-Schlatter disease (osteochondrosis of the tibial tubercle) is a common cause of anterior knee pain in sports-practicing adolescents. 1,2 Traditionally, it is treated with restriction from sports alone or in conjunction with undertaking physiotherapy. The goals of conservative treatment are to lessen the stress on the tibial tubercle and to reduce the tension in the quadriceps muscle.…”
mentioning
confidence: 99%
“…A proportion of teenagers are prevented from participating in sports for a prolonged period as a result of the condition, and some have persisting knee pain into adulthood. 2 Conservative treatment with rest, lidocaine injections, steroid injections, cylinder casts, and infrapatellar straps has been proposed for adults with continued symptoms. 4 Surgical treatment is indicated if they do not respond to conservative measures.…”
mentioning
confidence: 99%
“…Recently, Pagenstert et al have reported a satisfactory result after treatment of refractory OSD by reduction osteotomy of tibial tubercle [ 17 ]. Also, there was a case report showing the effect of repetitive percutaneous screw fixation of tibial tuberosity for adolescent OSD [ 18 ]. However, it should be noted that most of the studies were case reports with small subject numbers.…”
Section: Discussionmentioning
confidence: 99%